Comparative Analysis of Methods for Calculating Radiant Heating of Young Animals in Livestock Premises - A. V. Kuz’michev; D. А. Tikhomirov; A. V. Khimenko (Сельскохозяйственные машины и технологии, 2022)
The effectiveness of engineering systems at livestock enterprises is shown to be determined by the possibility of creating the required conditions where young animals are kept in interaction with external temperature parameters of their habitat. (Research purpose) The research aims to evaluate and choose a rational method for calculating radiant heat transfer in a system of surfaces with an arbitrary configuration that reflect the state of a biological object in a livestock room and the distribution of heat flows in the areas where young animals are located. (Materials and methods) The authors considered the conditions of a comfortable thermal regime for young animals and a physical model of animal heat transfer with the environment. The use of various methods for calculating heat transfer helped to determine the areas of change in the radiation panel temperature and the influence of the configuration and the system shell optical characteristics when creating comfortable conditions for keeping piglets. (Results and discussion) It was established that the computational model of heat transfer in a system of isothermal diffusely absorbing and radiating surfaces can be considered as an extension of existing computational methods. The model takes into account additional impact factors, including the influence of "hidden" surfaces through multiple reflections in a closed thermodynamic system. There is consistency between the results of heat transfer calculations by various methods, under the assumption that the system shell optical parameters are close to the characteristics of absolutely black body. (Conclusions) It was revealed that the system shell optical characteristics have a significant impact on the temperature regime of the irradiation panel surface, and the proposed computational model for determining the heated panel temperature regime in a system of isothermal diffusely absorbing and radiating surfaces can be applied to a wide range of agricultural premises of various configurations and geometries.